Inferior ST-Elevation Acute Myocardial Infarction or an Inferior-Lead Brugada-like Electrocardiogram Pattern Associated With the Use of Pregabalin and Quetiapine?. (July 2016) - Brunetti, Natale D.; Ieva, Riccardo; Correale, Michele; Cuculo, Andrea; Santoro, Francesco; Guaricci, Andrea I.; De Gennaro, Luisa; Gaglione, Antonio; Di Biase, Matteo
Abstract : The Brugada electrocardiogram pattern is characterized by coved-type ST-elevation (>2 mm) in the right precordial leads. We report the case of a 62-year-old man, with bipolar disorder, admitted to the emergency department because of dyspnea and chest discomfort. The patient was on treatment with pregabalin and quetiapine. Unexpectedly, electrocardiogram at admission showed diffuse ST-elevation, more evident in inferior leads, where a Brugada-like pattern was present. The patient underwent coronary angiography with a diagnosis of suspected acute coronary syndrome. Coronary angiography, however, showed mild coronary artery disease not requiring coronary angioplasty. Echocardiography did not reveal left ventricular dysfunction or pericardial effusion. Troponin levels remained normal over serial controls. Eventually, chest radiography showed lung opacities and consolidation suggestive for pneumonia. To the best of our knowledge, this is one of the first cases showing a transient Brugada-like electrocardiogram pattern in inferior leads, probably amplified by the administration of pregabalin and quetiapine.